Analysis of the Influence of the Hybrid Work System on Employee Productivity and Job Satisfaction at KOMPAS Gramedia in the Journalists and Editors Division - Farida, Ida (Jurnal Pro Hukum : Jurnal Penelitian Bidang Hukum Universitas Gresik, 2025)
This study aims to analyze the influence of the hybrid work system on the productivity and job satisfaction of journalists and editors at KOMPAS Gramedia. The background of the research departs from the post-pandemic global phenomenon that has shifted traditional work patterns to flexible models, as well as specific problems in the media industry that face deadline pressure, intensive coordination needs, and the risk of blurring working hours. The research method uses a quantitative approach with qualitative support. Data was collected through questionnaires of 100 respondents and interviews with a number of editors and journalists. The independent variable is hybrid work, while the dependent variable includes productivity and job satisfaction. The analysis was carried out by multiple linear regression and thematic analysis on interview data.The results of the study show that hybrid work has a significant positive effect on productivity and job satisfaction. Average productivity scores are higher than job satisfaction, indicating that location flexibility can improve performance, but job satisfaction is still constrained by digital coordination and flexible working hours. These findings show that the success of the implementation of hybrid work is not only determined by flexibility, but also by organizational policies that govern coordination and work-balance.